Delineation of the Arm Blood Vessels Utilizing Hyperspectral Imaging to Assist with Phlebotomy for Exploiting the Cutaneous Tissue Oxygen Concentration - Fouad Aref, Mohamed Hisham; Sharawi, Amr A.R.; El-Sharkawy, Yasser H. (Photodiagnosis and photodynamic therapy, 2021)
•Photonic technologies play a vital role in medical applications.•Hyperspectral imaging (HSI) system is a rising innovation that can beutilized to build a highly sensitive, non-invasive, and tissue hemoglobinimmersion map.•The ideal wavelength to reveal the oxygenated arteries was 460 nm, andthe ideal wavelength to reveal the de-oxygenated veins was 750 nmregarding the oxygen variations.•HSI is a prospective technique to assist with phlebotomy, vascularapproach, and may permit future surgical or pharmacological intercessionshat titrate or limit ischemic injury continuously. The estimation of tissue oxygenation is vital in the diagnosis and therapeutic evaluation of a huge assortment of diseases. The hyperspectral (HS) imaging system is a rising innovation that can be utilized to build a highly sensitive, non-invasive, and tissue hemoglobin immersion map. As a result of the urgent need to design and implement early detection devices and applications for the COVID-19 pandemic, we propose building a non-invasive custom optical imaging system to assist with phlebotomy and vascular approach to survey the reliability of blood oxygen saturation (SpO2) levels recovered from spectral images. HS images were gathered from 15 healthy subjects without previous medical history complications and with an average age range of 20 to 38 years, who were undergoing phlebotomy. The forearm was vigorously illuminated utilizing an HS camera with polychromatic source light of spectrum range (400∼980 nm). Spectroscopic reflectance images were caught by a focal plane exhibit for the region of interest (ROI). Then the custom algorithm comprising normalization and moving average filtering for noise removal was applied, followed by K-mean clustering for image segmentation to visualize and highlight the arteries and the veins in the investigated forearm. The investigations show that after normalization of the recorded signal from the HS camera of the participating subjects it was noticed that at wavelength of 460 nm the oxygenated arteries had a stronger signal than the de-oxygenated veins, and at a wavelength of 750 nm the de-oxygenated veins had a stronger signal than the oxygenated arteries. Thus, the ideal wavelength to reveal the oxygenated arteries was 460 nm, and the ideal wavelength to reveal the de-oxygenated veins was 750 nm. HSI is a prospective technique to assist with phlebotomy and non-contact oxygen saturation approach. Additionally, it may permit future surgical or pharmacological intercessions that titrate or limit ischemic injury continuously.